Musculoskeletal Symptoms Following COVID-19 Infection and Vaccination: An Observational Study - Adwan, Marwan Hmoud; Rahhal, Sara O; Abdulhameed, Jude J; AbuHelal, Ayman (Jordan Medical Journal, 2025)
Background: The global pandemic caused by COVID-19 has led to numerous reports of musculoskeletal (MSK) symptoms occurring after infection or vaccination. However, the precise prevalence of MSK symptoms in individuals following COVID-19 infection/vaccination remains uncertain. Methods: This observational study involved 46 patients who developed MSK symptoms after experiencing COVID-19 infection or vaccination. Results: The study group comprised 37 females (80.4%) and 9 males (19.6%) with an average age of 48.6±12.4 years (median 47.5 years). Among the participants, 25 patients (54%) developed symptoms after infection, while 21 patients (46%) reported symptoms after vaccination. The duration of symptoms ranged from 2 to 65 weeks, and the onset of symptoms occurred between 1-182 days following infection/vaccination (median 7 days). The small joints of the hands and feet were the most frequently affected (50%), followed by the wrists (47.8%) and knees (41.3%). Notably, approximately 50% of cases experienced complete resolution of symptoms. Additionally, individuals with pre-existing arthritis may experience exacerbation of their symptoms following infection/vaccination. Conclusion: This study reveals that MSK symptoms can manifest after COVID-19 infection/vaccination, with the small joints being the most commonly affected. These findings emphasize the importance of comprehending and monitoring MSK symptoms in individuals post-COVID-19 infection/vaccination to provide appropriate medical care and management.